Determination of cadmium in agricultural soils of Pallatanga canton, province of Chimborazo, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2020)
This investigation had the purpose of determining the presence of cadmium in agricultural soils, for which 6 sampling stations were selected in two cultivation systems that were found located in three altitudinal floors. Cadmium quantification was performed using the atomic absorption spectrophotometry to flame method, and the following methods were used to characterize the soil: Munsell tables, Feel, AS05, indirect volatilization gravimetry; and additionally, two multiparametric were used to determine pH and electrical conductivity. Cd variability was shown to differ with culture systems and altitudinal floors with values between 0,5 mg/kg to 1,0 mg/kg. Being 94% of the samples who exceeded the national maximum permissible limit, where in addition the correlation of cadmium with the physicochemical properties of the soil had an affinity with pH and organic matter.
Keywords: Soil; Cadmium; Agriculture; Altitudinal floor